Pertumbuhan Ikan Koi (Cyprinus Rubrofuscus) pada Sistem Vertiqua Biofikal Atas - Kurnia Candra Dwi Saputra; Ujang Dindin; Novita MZ (Habitat: Jurnal ilmiah ilmu Hewani dan Peternakan, 2024)
Limited land resources are a problem for fisheries, especially in urban areas. So the need for a new innovation in the field of fisheries for cultivation. Vertiqua (Vertical Aquaculture) is an innovation in vertical cultivation in limited land and water. The Vertiqua system as a cultivation medium has not been effective in increasing fish growth due to slow growth and high ammonia levels. Therefore, innovation is needed to increase the effectiveness of Vertiqua, namely by using the upper biofical filter. The data used to analyze is descriptive analysis by describing and describing the data that has been collected. Growth in length, weight, and survival, length-weight relationship, daily length growth rate, daily weight growth rate, and water quality were calculated using existing formulas. Comparative testing of growth was calculated using the T-test on the Mini Tab application. The results of the research showed that the top filter biofical vertiqua was able to increase the growth of koi fish. The growth value of the top biofical filter vertiqua is effective when compared to the soil pond. this is indicated by the value P<0.05. The upper biofical filter vertiqua system is also able to maintain the stability of water quality and suppress ammonia levels so that fish growth and survival are good. The vertiqua system with the upper biofical filter has an effect on fish growth, this is supported by the upper biofical filter, which is able to maintain water quality and suppress ammonia levels so that fish are not stressed and feed can be utilized properly.